2013
DOI: 10.1128/aem.00487-13
|View full text |Cite
|
Sign up to set email alerts
|

Use of Agent-Based Modeling To Explore the Mechanisms of Intracellular Phosphorus Heterogeneity in Cultured Phytoplankton

Abstract: There can be significant intraspecific individual-level heterogeneity in the intracellular P of phytoplankton, which can affect the population-level growth rate. Several mechanisms can create this heterogeneity, including phenotypic variability in various physiological functions (e.g., nutrient uptake rate). Here, we use modeling to explore the contribution of various mechanisms to the heterogeneity in phytoplankton grown in a laboratory culture. An agent-based model simulates individual cells and their intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
(78 reference statements)
2
8
0
Order By: Relevance
“…The sensitivity analysis revealed that the magnitude of the error is very sensitive to the maximum nitrate storage quota Q max , which plays a key role in controlling the range of internal nitrate that an individual cell can carry and therefore modulates the variability between individuals. This result is consistent with Fredrick et al (2013), who explored the relative contribution of several biological parameters to intra-population variability in terms of the internal phosphorus content of the planktonic diatom Thalassiosira pseudonana. They found that the variability of Q max was the main factor influencing intra-population heterogeneity, in agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The sensitivity analysis revealed that the magnitude of the error is very sensitive to the maximum nitrate storage quota Q max , which plays a key role in controlling the range of internal nitrate that an individual cell can carry and therefore modulates the variability between individuals. This result is consistent with Fredrick et al (2013), who explored the relative contribution of several biological parameters to intra-population variability in terms of the internal phosphorus content of the planktonic diatom Thalassiosira pseudonana. They found that the variability of Q max was the main factor influencing intra-population heterogeneity, in agreement with our results.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, Bucci et al (2012) studied variability in terms of phosphate cell quota in enhanced biological phosphorus removal and showed that the Eulerian model can produce approximately the same results as the Lagrangian version only if the value of the growth rate is reduced by 55%. In a similar experiment, Fredrick et al (2013) showed that the Eulerian formulation overestimates biomass by > 40%. It is noticeable that in these studies, differences among individuals emerged from phenotypical variability introduced explicitly in the Lagrangian model by randomizing cell parameters during cell division.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In other words, most quota distributions have a notable positive skew even after logarithmic transformation. The phenomenon of high-quota cells driving population heterogeneity has been shown previously in a diatom growth model for P utilization when modeled under conditions of non-limiting nutrient availability (Fredrick et al, 2013). Such results are consistent with Si's putatively non-essential nature in Synechococcus and also the general availability (non-limiting nature) of S in the marine environment.…”
Section: Potential Causes For Si Variability In Synechococcussupporting
confidence: 86%
“…Today, the range of agent-based model applications is quite broad. For example, these models have been used to represent the Ras-MAPK [17] and NF-kB [38] intracellular signalling pathways, Escherichia coli cytoplasm dynamics [30], bacterial phenotypic switching [46], epithelial host-pathogen interactions [45], cancer systems biology [29], development of restenosis in blood vessels [12], autophagy dynamics and sub-mitochondrial heterogeneity [8], intracellular phosphorus heterogeneity in cultured phytoplankton [16], oxygen metabolism in aerobic-anaerobic respiration [5], and the design of cellulase systems [3].…”
Section: Abm For Biomolecular Modellingmentioning
confidence: 99%